iRGD conjugated nimbolide liposomes protect against endotoxin induced acute respiratory distress syndrome - Pooladanda, Venkatesh (Nanomedicine, 2021)
Acute respiratory distress syndrome (ARDS) is a deadly respiratory illness associated with refractory hypoxemia and pulmonary edema. The recent pandemic outbreak of COVID-19 is associated with severe pneumonia and inflammatory cytokine storm in the lungs. The anti-inflammatory phytomedicine nimbolide (NIM) may not be feasible for clinical translation due to poor pharmacokinetic properties and lack of suitable delivery systems. To overcome these barriers, we have developed nimbolide liposomes conjugated with iRGD peptide (iRGD-NIMLip) for targeting lung inflammation. It was observed that iRGD-NIMLip treatment significantly inhibited oxidative stress and cytokine storm compared to nimbolide free-drug (f-NIM), nimbolide liposomes (NIMLip), and exhibited superior activity compared to dexamethasone (DEX). iRGD-NIMLip abrogated the LPS induced p65 NF-κB, Akt, MAPK, Integrin β3 and β5, STAT3, and DNMT1 expression. Collectively, our results demonstrate that iRGD-NIMLip could be a promising novel drug delivery system to target severe pathological consequences observed in ARDS and COVID-19 associated cytokine storm.